HUMAN CAPITAL AND TECHNOLOGY IN THE GROWTH OF ECONOMIC STRUCTURE - Leite, Deyvid W.; C.B. Cardoso, Leonardo (Investigación Económica, 2022)
ABSTRACT Recognizing a relationship between economic structure and growth is important but not enough for screening policies. For policy purposes, the second natural step is to understand how structural change proceeds, indicating which variables explain the economic structure. We shed light on this debate analyzing the relationship between economic structure, human capital, and technology investment at the national level. We use a new measure of the economic structure —the Economic Complexity Index— in a fixed-effects panel with 97 countries from 1996 to 2015. Results indicated that a more complex structure is related to higher levels of human capital, investment in technology, and trade openness. Regarding human capital, the democratization of education plays a role, but its quality is the centerpiece for structural change. CAPITAL HUMANO Y TECNOLOGÍA EN EL CRECIMIENTO DE LA ESTRUCTURA ECONÓMICA RESUMEN Reconocer la relación entre la estructura económica y el crecimiento es importante pero no suficiente para las políticas de selección. Para propósitos de política, el segundo paso natural es entender cómo procede el cambio estructural, indicando cuáles variables explican la estructura económica. Contribuimos a este debate analizando la relación entre estructura económica, capital humano e inversión en tecnología a nivel nacional. Usamos una nueva medida de la estructura económica, el índice de complejidad económica, en un panel de efectos fijos con 97 países de 1996 a 2015. Los resultados mostraron que una estructura más compleja está relacionada con niveles más altos de capital humano, inversión en tecnología y apertura comercial. En cuanto al capital humano, la democratización de la educación juega un papel, pero su calidad es la pieza central para el cambio estructural.